Degenerated ground-states in a spin chain with pair interactions: a characterization by symbolic dynamics. (30th December 2016) - Corona, L A; Salgado-García, R
Abstract: In this paper we study a class of one-dimensional spin chain having a highly degenerated set of ground-state configurations. The model consists of spin chain having infinite-range pair interactions with a given structure. We show that the set of ground-state configurations of such a model can be fully characterized by means of symbolic dynamics. Particularly we found that the set ground-state configurations define what in symbolic dynamics is called sofic shift space . Finally we prove that this system has a non-vanishing residual entropy (the topological entropy of the shift space), which can be exactly calculated.